PRESCRIBING PATTERN OF ANTIDEPRESSANTS AMONG PATIENTS WITH DEPRESSION IN MENTAL HOSPITAL OF NEPAL AND ITS COMPARISON WITH INTERNATIONAL GUIDELINES (International Journal of Food and Nutritional Sciences, 2021)
Background: One of the main mental illnesses that is about to become more prevalent is depression. Research on the optimal prescription of antidepressants is crucial since improper use of these medications can exacerbate depression symptoms.The purpose of this study is to examine the antidepressant prescribing patterns of individuals who have been diagnosed with depression and to see if they align with suggested standards.Methods: Mental Hospital Patan, Nepal was the site of this retrospective investigation. Enrolled were all patients (≥18 years old) who had been prescribed at least one antidepressant and had a diagnosis of depression. Patients' records were chosen on a daily registration basis between January 15, 2018, and May 14, 2018. The purpose of the data gathering form was to document hospital eligible patient information. Version 21 of the Statistical Package for the Social Sciences (SPSS) was utilized to analyze the data.